Effect of phase transformation strain on residual stress analysis results of multi pass bead on plate specimen - Nobuyoshi YANAGIDA (The Japan Society of Mechanical Engineers, 2016)
The weld pass sequence generally affects residual stress profiles. In this study, the residual stress profiles of bead on plate specimens were analytically and experimentally examined. The material used in this study was the low alloy steel SQV2A (JIS G 3120), which is equivalent to ASTM A533. Phase transformation usually occurs around the welded area in SQV2A and also affects the residual stress profiles. To estimate residual stress, three specimens were fabricated. One was single pass bead welded and the others were five pass and nine pass bead welded. To predict the residual stress profiles numerically, temperature history analyses and residual stress analyses were conducted. Phase transformation strain was taken into consideration as a component of thermal strain. Analysis results show that the amount of longitudinal tensile stress at the center of the last pass area is lower than that at the edges. The longitudinal residual stress profiles around the last pass area of the five pass and nine pass specimens are similar to that around the weld pass area of the single pass specimen. The longitudinal tensile stress in the previous passes area is higher than that at the center of the last pass in the five pass and nine pass specimens. These analysis results suggest that the phase transformation strain affects the residual stress profiles around the last pass area in each specimen. To validate the analysis results, residual stress of these specimens were measured by using the strain relief method. The analysis results with the phase transformation strain consideration are in agreement with the experiment results. Accordingly, these analysis results can be considered valid.